Revision of Valanginian Steinmanellinae bivalves from the Neuquén basin, West-central Argentina, and their biostratigraphic implications - Lazo, Dario Gustavo (2013)
We present a new species of Steinmanella Crickmay from the Valanginian of the Neuquén Basin, west-central Argentina, and at the same time update a Valanginian-earliest Barremian bivalve zonation which is integrated into the local, Chilean and European standard ammonoid zonations. Steinmanella caicayensis sp. nov. presents a moderately inflated shell, a subtriangular outline, well-developed carinaeand a straight to moderately convex anterior margin. Steinmanella is very abundant in the Tithonian-Barremian interval in the basin and thus provides an ideal opportunity to perform detailed taxonomic and stratigraphic studies; a former zonation based on these trigonioids is here revised and expanded with a thorough revision of Valanginian occurrences based on new material. Two new zones are proposed, namely the S.quintucoensis and S.caicayensis zones, encompassing Valanginian times. The proposed bivalve zonation encompassing the Valanginian-earliest Barremian time interval can be useful in correlating with other southwestern Gondwanan regions, such as Perú, Chile, South Africa, Tanzania, and India, where Steinmanella has been recorded.